2015
DOI: 10.1177/0308022614562400
|View full text |Cite
|
Sign up to set email alerts
|

An intervention to support professional driver retirement transition: Results of a pilot study for older taxi drivers in Singapore

Abstract: Introduction: Older taxi drivers in Singapore face mandatory retirement at 73 years of age, often marked by the simultaneous loss of the worker and driver roles. The Driver Retirement Program was developed as an intervention to support this transition. Method: A pre-and post-experimental design was conducted with retired 73-year-old, male taxi drivers (n ¼ 15) to investigate the hypotheses: (i) the Driver Retirement Program would increase activity participation (e.g. time use) and wellbeing (e.g. mood) outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…The findings from the hypotheses support empirical findings of Wang and Hesketh (2012) that retiree"s participation in psychological and social activities such as family support systems positively affects retirement preparedness because they provide companionship. This was further in concurrence to the results of Chan, Gustafsson and Liddle (2015) that effective retirement planning programmes enhance psychosocial resources of an individual and hence improve adaptation in retirement transition. Indeed, the empirical findings that engagement in psychosocial programmes had a significant positive effect on retirement preparedness are particularly important in assisting individual employees to plan for separation from employer organization and subsequent life in retirement.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The findings from the hypotheses support empirical findings of Wang and Hesketh (2012) that retiree"s participation in psychological and social activities such as family support systems positively affects retirement preparedness because they provide companionship. This was further in concurrence to the results of Chan, Gustafsson and Liddle (2015) that effective retirement planning programmes enhance psychosocial resources of an individual and hence improve adaptation in retirement transition. Indeed, the empirical findings that engagement in psychosocial programmes had a significant positive effect on retirement preparedness are particularly important in assisting individual employees to plan for separation from employer organization and subsequent life in retirement.…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, employee retirement planning should not be a concern only during the second half of employee"s life, but rather from start of employment (Ekerdt, 2004;Phua & McNally, 2008). Effective retirement planning programmes should enhance psychosocial resources of an individual resulting to improved adaptation in retirement transition (Shultz & Wang, 2007;Chan, Gustafsson & Liddle, 2015). adjustment process by viewing the retirement transition as one where individual, contextual and psychological factors interact (Donaldson, Earl, & Muratore 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the claimed benefits of retirement preparation programs, there is a dearth of evaluation of such programs. A literature search revealed only a few relevant studies evaluating group or individual interventions aimed at promoting retirees’ coping strategies in order to enhance happiness and buffer against depression (Chan, Gustafsson, & Liddle, 2015; Goold, 2007; Liddle et al, 2014). For example, Goold (2007) presented a study that included 370 retirees, 65–85 years of age, living in the Gold Coast (Australia).…”
Section: Planning and Preparation For Retirementmentioning
confidence: 99%
“…Participants indicated that they enjoyed the program and learned from it. A second study (Chan et al, 2015) evaluated a complex intervention using a prospective experimental design with a single group of 20 taxi drivers in Singapore. The results presented significant improvement in mood, self-efficacy, and individual goal satisfaction.…”
Section: Planning and Preparation For Retirementmentioning
confidence: 99%
“…Although many individuals with health conditions can learn to drive, resume driving after an acquired incident, or maintain their driving despite age-related health declines, the complex skill level required to control a vehicle safely and independently is not always attained. The final papers examine occupational therapy interventions to support driving cessation, with one (Liddle et al., 2015) describing the experiences of peer leaders who run educational support groups for older people undergoing driving cessation, and another (Chan et al., 2015) reporting on how a driver retirement programme can support older taxi drivers’ transition from their worker and driver roles.…”
mentioning
confidence: 99%